Acute Kidney Injury (AKI) SEBAGAI FAKTOR PREDIKTOR KEMATIAN PASIEN DI ICU RSUP DR SARDJITO - , Ronggo Baskoro; , Dr. Calcarina Fitriani RW, Sp.An, KIC. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : AKI still have a high mortality rate and often undiagnosed. Prediction and diagnosis of AKI can be done with the RIFLE criteria. Early detection and management of AKI could reduced mortality rate. There is no data on the incidence of AKI in ICU RSUP DR Sardjito. We conducted the study to determine AKI as mortality predictor in patients admitted to the ICU RSUP DR Sardjito. Method : Design of this study was retrospective cohort. Subjects are 112 and all patients in the ICU department of RSUP DR Sardjito started in June 2013 â October 2013. Inclusion criteria were patients over 18 years and have a complete medical records, whereas the exclusion criteria were patients who had been diagnosed with Chronic Kidney Disease (CKD) with hemodialysis either conservative therapy. Severity progres of AKI in ICU RSUP DR Sardjito. Data analysis using logistic regression odds ratios to see the impact of the significant characteristics of the data values (p <0.05) from group AKI and non-AKI. Multivariable model used the model enter. AKI. A p value of <0.05 was considered statistically significant. Result : AKI is a mortality predictor in patients admitted to the ICU. The value of the RR (relative risk) is 8.0, which means that the patients in the AKI group had a 8.0 times greater likelihood of death than patients in the non-AKI group. It also found that the mortality rate of patients suffering from AKI with risk criteria (R) is 31.7%, Injury criteria (I) 75%, and Failure (F) 71.4%. Conclusion : AKI can be used as mortality predictor in patients admitted to the ICU.